Optimized Dimension Design of Catalytic Chamber of a 10 N Thruster - Sajjad Davari; Hadiseh Karimaei; Mohammad Reza Salimi; Hassan Naseh (فصلنامه علوم و فناوری فضایی, 2023)
In this paper, the catalyst bed of a 10 N hydrazine monopropellant thruster was designed. The catalyst bed is including iridium granules, which is used to decompose the hydrazine in monopropellant thruster. Hydrazine must be decomposed almost completely in the catalytic chamber, because it is a carcinogenic chemical fuel and on the other hand, achieving the maximum power from the thruster is also an important goal. As a result, the effect of change in catalytic chamber length on the mass fraction of chemical species including hydrazine, ammonia, nitrogen, and oxygen was studied. Also, after determining the length of the catalytic chamber, the diameter of the nozzle throat corresponding to the same length was determined.